Penggunaan Slang Words (Gaya Bahasa Slang) Melalui Aplikasi Tik Tok di Kalangan Mahasiswa - Wiyanti, Dede Tresna; Setiawati, Neysa Putrianie; Zakaria, Saifulah; Soemarwoto, Rini Susetyawati; Indrawardana, Ira (Biokultur, 2024)
The rapid development of technology information affects the culture of society. Social media as a product of today's development has become a necessity. The need for social media has an impact on the need for la nguage which has led to the development of slang styles in cyberspace. Slang language styles have become part of the language used daily, including students. Tik tok as one of the most popular applications is one of the applications with the widespread use of slang language styles. This research will discuss how the use of slang words among Anthropology students at Padjadjaran University class of 2019. The study was carried out using the classification of slang language styles according to Alwasilah (1993), namely popular adaptation, expansion of meaning, new vocabulary, and reaction to serious diction. The method used in this research is qualitative with descriptive and content analysis. The findings from this study explain the style of slang in the tick tok accounts of Anthropology University of Padjadjaran students class of 2019 which have been classified. The use of slang in the tik tok account of Anthropology University of Padjadjaran students class of 2019 illustrates communication patterns that tend to have relatively the same verbal repertoire and social media culture so that users can understand one another.